Safe and sustainable business models for water reuse in aquaculture in developing countries - Amoah, Philip; Gebrezgabher, Solomie A.; Drechsel, Pay (International Water Management Institute, 2021)
Wastewater-fed aquaculture has a long history, especially in Asia. This report examines three empirical cases of integrated wastewater treatment and aquaculture production. From an aquaculture entrepreneur’s perspective, the combination of fish farming and wastewater treatment in common waste stabilization ponds allows significant savings on capital (pond infrastructure) and running costs (wastewater supporting fish feed). On the other hand, the treatment plant owner will have the benefit of a partner taking over plant maintenance. Given the importance of food safety and related perceptions, the report is focusing on innovative business models where the marketed fish is not in direct contact with the treated wastewater, but only the brood stock or fish feed. The financial analysis of the presented systems shows profitable options for the fish farmer, operational and in part capital cost recovery for the treatment plant, and as the treatment plant operators can stop charging households a sanitation fee, eventually a triple-win situation for both partners and the served community.